Life imprisonment in Australia: restoring a hope of release and the Phuong Ngo case - Anderson, John (Life Imprisonment in Asia, 2023)
In this chapter, following an overview of the differential schemes of life imprisonment in the several Australian jurisdictions there is a specific focus on New South Wales (NSW) as the outlier where the prospect of release from a natural life sentence is solely restricted to the exercise of the Royal prerogative of mercy. The practical operation of this sentence is examined through the special case example of Phuong Ngo, who was convicted of the only contract political assassination in Australia and sentenced to life imprisonment in November 2001. The Royal prerogative of mercy as the only potential release mechanism does not offer a reasonable prospect for Ngo’s conditional liberty as it is only exercised in the most extraordinary circumstances—a threshold requirement too vague to be meaningful in practice. One final avenue for possible relief is a communication to the United Nations Human Rights Committee for a remedy requesting legislative repeal or amendment to bring the indeterminate sentence into line with Australia’s international human rights obligations under the International Covenant on Civil and Political Rights. Overall, the ongoing journey in Ngo’s case example highlights that life imprisonment in NSW precludes the attainment of important sentencing principles of proportionality and human dignity.